2016
DOI: 10.2147/jpr.s117885
|View full text |Cite
|
Sign up to set email alerts
|

Improving pain care through implementation of the Stepped Care Model at a multisite community health center

Abstract: PurposeTreating pain in primary care is challenging. Primary care providers (PCPs) receive limited training in pain care and express low confidence in their knowledge and ability to manage pain effectively. Models to improve pain outcomes have been developed, but not formally implemented in safety net practices where pain is particularly common. This study evaluated the impact of implementing the Stepped Care Model for Pain Management (SCM-PM) at a large, multisite Federally Qualified Health Center.MethodsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 43 publications
0
47
0
Order By: Relevance
“…Multidisciplinary education has been shown to empower rheumatoid arthritis patients to manage their condition and reduce disease activity in the longer term . We hypothesize that addressing these factors, for example through individualized interventions supporting patients to manage their oral and ocular dryness symptoms and with nonpharmacologic interventions such as exercise , pain management , and cognitive behavioral therapy for sleep disturbances , patients may feel more patient empowered. Modes of delivering these interventions need to be considered, and digital technologies, such as the use of mobile applications, can be used to empower patients to take charge of their own health and used as an adjunct to face‐to‐face care.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary education has been shown to empower rheumatoid arthritis patients to manage their condition and reduce disease activity in the longer term . We hypothesize that addressing these factors, for example through individualized interventions supporting patients to manage their oral and ocular dryness symptoms and with nonpharmacologic interventions such as exercise , pain management , and cognitive behavioral therapy for sleep disturbances , patients may feel more patient empowered. Modes of delivering these interventions need to be considered, and digital technologies, such as the use of mobile applications, can be used to empower patients to take charge of their own health and used as an adjunct to face‐to‐face care.…”
Section: Discussionmentioning
confidence: 99%
“…A power analysis for a paired-samples t test assuming 80% statistical power, significance level of 0.05, and standard deviation of 1 shows the minimum detectable effect is 0.13 from pre to post. Similar or larger effect sizes have been determined for changes in providers' opioid prescribing knowledge, attitudes, and beliefs, self-efficacy, and opioid management practices following other opioid management QI projects [14,29].…”
Section: Data Analysis Analytic Planmentioning
confidence: 63%
“…While there have been some studies of opioid stewardship in primary care settings [11][12][13][14][15][16], most have been within one health care system and have not examined differences across systems and practices. Additionally, only a few of these studies examined implementation explicitly, which is a critical component of putting evidence-based interventions into practice.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a total of 227 reviewed studies meeting all inclusion criteria were identified in this scoping review (Fig 1). [2][3][4][5][6][33][34][35][36][37][38][39][40][41][42][45][46][47][48][49][51][52][53][54][55][56][57][58][59][60][63][64][65][66][67][68][69][70][71][72][73][103][104][105][106][107][108][109][110][111][113][114][115][116][117][118][119][120][121][122][123]…”
Section: Eligibility Screeningmentioning
confidence: 99%